Purity and the Forming of Religious Traditions in the Ancient Mediterranean World and Ancient Judaism - Frevel, Christian; Nihan, Christophe (Dynamics in the History of Religions, 2012)
Focusing on concepts, practices and images associated with purity in the ancient Mediterranean, this volume contributes new aspects to the current discussion about the forming of religious traditions, from a comparative perspective that acknowldges individual developments, mutual exchanges, as well as transcultural processes.; Readership: Scholars interested in the history of religions, religious contacts and social-cultural interactions in Antiquity, purity and impurity in the ancient Mediterranean world, as well as mechanisms of social control and regulation in ancient societies.